2006
DOI: 10.1097/01.fbp.0000197456.63150.cd
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Pavlovian conditioning with nicotine as the conditional stimulus varies as a function of the number of conditioning trials and unpaired sucrose deliveries

Abstract: In rats, the pharmacological (interoceptive) effects of nicotine can serve as a signal (conditional stimulus) in a Pavlovian (classical) conditioning task. In this task, nicotine administration (0.4 mg base/kg, subcutaneous) is typically paired with intermittent access to a liquid sucrose unconditional stimulus; sucrose is withheld on saline sessions. An increase in sucrose receptacle entries (goal tracking) on nicotine sessions indicates conditioning. Given our limited understanding of the functional relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 43 publications
7
35
1
Order By: Relevance
“…Experiment 1 of the present report extends this research by showing that a fading procedure is not required for a 0.2 mg/kg dose of nicotine to function as interoceptive CS. Although one must be cautious when comparing across studies, there does not appear to be any obvious difference in acquisition of the discrimination between the present study and previous research using 0.4 mg/kg nicotine [36]. Further research, however, is needed to directly assess whether this dose of nicotine affects acquisition and/or maintenance of conditioned responding.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Experiment 1 of the present report extends this research by showing that a fading procedure is not required for a 0.2 mg/kg dose of nicotine to function as interoceptive CS. Although one must be cautious when comparing across studies, there does not appear to be any obvious difference in acquisition of the discrimination between the present study and previous research using 0.4 mg/kg nicotine [36]. Further research, however, is needed to directly assess whether this dose of nicotine affects acquisition and/or maintenance of conditioned responding.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous research from our laboratory has shown that 0.4 mg/kg of nicotine paired reliably with sucrose acquires the ability to control a goal-tracking CR [4,36]. Further, a 0.2 mg/kg dose of nicotine also served as an interoceptive CS using a fading procedure [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using head entries into the sucrose receptacle before the fi rst sucrose delivery as a measure of conditioning (i.e., goal tracking; Boakes, 1977 andFarwell andAyres, 1979), nicotine readily served as a conditional stimulus as evidenced by increased dipper entries on nicotine compared to saline sessions. Importantly, when a group of rats had access to sucrose on both nicotine and saline sessions, differential conditioned responding did not develop (Wilkinson et al, 2006b).…”
Section: Introductionmentioning
confidence: 96%
“…Nicotine can also cue when a discrete light conditional stimulus will not be followed by sucrose, thereby serving as a negative drug feature (Bevins et al, 2006). Nicotine has also recently been shown to serve as an interoceptive contextual conditional stimulus for access to sucrose in rats (Besheer et al, 2004 andWilkinson et al, 2006b). Briefl y, in that research, a subcutaneous (s.c.) injection of 0.4 mg base/ kg nicotine or saline was given 5 min before placement in a conditioning chamber.…”
Section: Introductionmentioning
confidence: 99%